Perception of Fairness of Interaction in Handling Complaints of Users of Travel Agency Services: Evidence from Serbia and Croatia - Jelena Jevtić; Slavica Tomić; Ksenija Leković (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2021)
Service-dominant logic observes the user as a co-creator of value in the process of providing services. In the case of a complaint, as a result of dissatisfaction, the user and the travel agency become a co-creator of the value of service recovery. The perception of interactionist fairness is one of the determinants of a user's complaint behaviour. Interactionist fairness is seen in the extent to which users consider to be treated fairly in terms of their interaction with a travel agency employee during the service recovery process. The research presented in this paper is based on determining the differences in perception of fairness of interaction in handling complaints of users of travel agency services in terms of their socio-demographic characteristics. The survey was conducted on a sample that included 297 respondents from the territory of Serbia and Croatia. The proposed hypotheses were tested using the Mann - Whitney U test and the Kruskal-Wallis test. The purpose of this paper is to point out to travel agencies the importance of users' reactions to unsatisfactory service as a kind of reflection of cooperation in service recovery.
Keywords: L83; Z32; 330; user; travel agency; complaint behaviour; perception; socio-demographic characteristics